Nurses' work in relation to patient health outcomes: an observational study comparing models of primary care - Nicolette Sheridan; Karen Hoare; Jenny Carryer; Jane Mills; Sarah Hewitt; Tom Love; Timothy Kenealy; The Primary Care Models Study Group (BMC, 2024)
Abstract Background Māori are over-represented in Aotearoa New Zealand morbidity and mortality statistics. Other populations with high health needs include Pacific peoples and those living with material deprivation. General practice has evolved into seven models of primary care: Traditional, Corporate, Health Care Home, Māori, Pacific, Trusts / Non-governmental organisations (Trust/NGOs) and District Health Board / Primary Care Organisations (DHB/PHO). We describe nurse work in relation to these models of care, populations with high health need and patient health outcomes. Methods We conducted a cross-sectional study (at 30 September 2018) of data from national datasets and practices at patient level. Six primary outcome measures were selected because they could be improved by primary care: polypharmacy (≥ 65 years), glucose control testing in adults with diabetes, immunisations (at 6 months), ambulatory sensitive hospitalisations (0-14, 45-64 years) and emergency department attendances. Analysis adjusted for patient and practice characteristics. Results Nurse clinical time, and combined nurse, nurse practitioner and general practitioner clinical time, were substantially higher in Trust/NGO, Māori, and Pacific practices than in other models. Increased patient clinical complexity was associated with more clinical input and higher scores on all outcome measures. The highest rates of preventative care by nurses (cervical screening, cardiovascular risk assessment, depression screening, glucose control testing) were in Māori, Trust/NGO and Pacific practices. There was an eightfold difference, across models of care, in percentage of depression screening undertaken by nurses and a fivefold difference in cervical screening and glucose control testing. The highest rates of nurse consultations afterhours and with unenrolled patients, improving access, were in PHO/DHB, Pacific, Trust/NGO and Māori practices. Work not attributed to nurses in the practice records meant nurse work was underestimated to an unknown degree. Conclusions Transferring work to nurses in Traditional, Health Care Home, and Corporate practices, would release general practitioner clinical time for other work. Worse patient health outcomes were associated with higher patient need and higher clinical input. It is plausible that there is insufficient clinical input to meet the degree of patient need. More practitioner clinical time is required, especially in practices with high volumes of complex patients.